Forgotten wars : Central and Eastern Europe, 1912-1916 - Borodziej, Włodzimierz; Górny, Maciej, 1976-; Tilbury, Jasper (Cambridge : Cambridge University Press, 2021)
Włodzimierz Borodziej and Maciej Górny set out to salvage the historical memory of the experience of war in the lands between Riga and Skopje, beginning with the two Balkan conflicts of 1912-1913 and ending with the death of Emperor Franz Joseph in 1916. The First World War in the East and South-East of Europe was fought by people from a multitude of different nationalities, most of them dressed in the uniforms of three imperial armies: Russian, German, and Austro-Hungarian. In this first volume of Forgotten Wars, the authors chart the origins and outbreak of the First World War, the early battles, and the war's impact on ordinary soldiers and civilians through to the end of the Romanian campaign in December 1916, by which point the Central Powers controlled all of the Balkans except for the Peloponnese. Combining military and social history, the authors make extensive use of eyewitness accounts to describe the traumatic experience that established a region stretching between the Baltic, Adriatic, and Black Seas.
This is a translated and updated publication of Nasza wojna. Tom 1. Imperia 1912-1916 written in Polish by Włodzimierz Borodziej and Maciej Górny and published by W.A.B. in 2014.
Title from publisher's bibliographic system (viewed on 19 Mar 2021).
Keywords: World War, 1914-1918 -- Campaigns -- Eastern Front; World War, 1914-1918 -- Causes